First-Time Experience in Owning a Dog Guide by Older Adults with Vision Loss. (September 2019) - Li, Kitsum; Kou, Jeffrey; Lam, Yvonne; Lyons, Patricia; Nguyen, Susan
Introduction: In spite of the vast amount of literature on pet therapy and dog companionship, limited studies exist on older adults with vision loss and the experience of owning a dog guide. The purpose of this study is to explore the facilitators and barriers of first-time ownership and utilization of a dog guide as experienced by older adults with vision loss. Methods: Data were gathered among seven participants using open-ended semistructured telephone interviews. Participants described their experiences related to owning a dog guide. Using phenomenological analysis, themes were extracted from verbatim transcriptions. Results: Through constant comparison methods, five themes emerged: increased responsibilities for new dog guide owners, changes in habits and routines, quick human–dog guide bonding, increase in community integration, and enhancement of autonomy through dog guide ownership. Discussion: The study results suggest that obtaining a dog guide increased the older adults with vision loss everyday engagement in community activities. The increased confidence in independent mobility may have led participants to engage in activities in unfamiliar environments, thus improving their autonomy, self-esteem, and physical abilities. These changes resulted in increased feelings of independence and freedom for the older adults with vision loss. Participants also revealed positive changes in their daily habits. Due to the increased physical ability and motivation needed to complete activities, making adjustments to owning a dog guide became easier. Furthermore, a human–dog guide bond was prevalent among all seven participants. Implications for practitioners: Themes extracted provide health practitioners and dog guide organizations insight into how owning dog guides may empower older adults with vision loss.